PUBLIC HOUSING POLICIES IN PERU 1946-2021 AND CONTRIBUTIONS TO A PUBLIC HOUSING POLICY 2021-2030 - Castillo-García, Rodolfo Francisco (2023)
This article is the product of academic research, personal refl ections, professional experiences, and normative and technical proposals of the author. It is a qualitative approximation to the study and systematization of public housing policies in Peru in the period 1946-2021, by representative institutions, by type of policies, and by type of political and economic reforms; and also is a proposal of some contributions for a public housing policy in the country 2021- 2030, with housing programs differentiated by social strata, by city size, and by natural regions. Keywords: housing – public housing policies – public policies